Implementasi Media Visual Terpersonalisasi (Personal Photograph) untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris pada Siswa Autis - Elisa Haddina; Rudiyanto Rudiyanto; Syahrul Efendi Lubis; Nadhira Yasmine Ahmad; Ricki Asi Erwindo Siahaan (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: Students with Autism Spectrum Disorder (ASD) face significant challenges in learning English vocabulary due to limitations in communication abilities, social interaction, and abstract information processing. This Community Service activity aims to improve English vocabulary mastery of students with special needs through the implementation of Personal Photograph learning media at SLBN Autis North Sumatra. Methodology: The program was implemented in three main stages: preparation (needs observation, teacher interviews, material preparation, and collection of students' personal photographs), implementation (socialization, training, learning activities, and mentoring), and evaluation (pre-test, post-test, observation, and questionnaire). The activity involved 20 students as active participants. Results: Results showed an increase in students' average vocabulary scores from 52.4 in the pre-test to 78.6 in the post-test, representing a 50.0% improvement. Student participation rate during the activity reached 90%, while teacher satisfaction with the program reached 92%. These findings indicate that the use of Personal Photograph media can significantly improve learning motivation, attention, and vocabulary retention in students with ASD. Conclusions: This media is considered practical, contextual, and potentially applicable on a sustainable basis in special education school settings. This program provides a tangible contribution to the development of inclusive and adaptive learning strategies for special education teachers.